The Indonesian Islamic Bank’s Spin-off: A Study in Regional Development Banks - Haribowo, Ismawati (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2017)
The Islamic banking spin-off became a major issue after the establishment of the Act No. 21 of 2008. The problem that arises according to this spin-off is the existence of sharia unit that owned by the regional development banks, which is almost the banks has a small size. This paper is going to evaluate the spin-off criteria are regional development banks, besides that this article is going to analyze the spin-off strategy that can use by sharia unit that owned by the regional development bank. The techniques that employed in this paper are ARIMA, simulation, and descriptive-qualitative. The result shows that there is no sharia unit can achieve the 50% share asset of its parents. There are also several strategies that can be used by the sharia unit. The main thing that should emphasize is the Islamic bank's spin-off is only one of the policies that can be taken to develop the Islamic banking industryDOI: 10.15408/aiq.v9i1.4308